2023
DOI: 10.1099/jgv.0.001824
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cellular autophagy by genotype 1 hepatitis E virus ORF3 protein

Abstract: Hepatitis E virus (HEV) egresses from infected hepatocytes as quasienveloped particles containing open reading frame 3 (ORF3) protein. HEV ORF3 (small phosphoprotein) interacts with host proteins to establish a favourable environment for virus replication. It is a functional viroporin that plays an important role during virus release. Our study provides evidence that pORF3 plays a pivotal role in inducing Beclin1-mediated autophagy that helps HEV-1 replication as well as its exit from cells. The ORF3 interacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
0
0
1
Order By: Relevance
“…In general, our results clarified that the whole process of autophagy flux in JEG-3 cells was inhibited by HEV infection. This is not consistent with previous studies, which is speculated that there are differences in the choice of HEV genotypes and cell lines [ 48 , 49 ]. Decreased autophagy may be more damaging when it occurs in trophoblast cells, whose invasive function is dependent on intracellular levels of autophagy, which is strongly associated with miscarriage [ 19 ].…”
Section: Discussioncontrasting
confidence: 94%
“…In general, our results clarified that the whole process of autophagy flux in JEG-3 cells was inhibited by HEV infection. This is not consistent with previous studies, which is speculated that there are differences in the choice of HEV genotypes and cell lines [ 48 , 49 ]. Decreased autophagy may be more damaging when it occurs in trophoblast cells, whose invasive function is dependent on intracellular levels of autophagy, which is strongly associated with miscarriage [ 19 ].…”
Section: Discussioncontrasting
confidence: 94%
“…Notably, erlotinib-based relative induction of autophagy is less pronounced in persistently HEV-infected cells, as HEV infection alone induces autophagy through inhibition of key kinases such as mTOR, protein kinase B (Akt1/2), and PIM1-3, which is consistent with previous publications ( 75 ). In particular, the structural protein pORF3 of HEV genotype 1 was found to induce cellular autophagy ( 76 ). The induction of autophagosomal structures, along with the previously discussed impaired lysosomal acidification and functionality upon HEV infection, promotes the pathway for viral release.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, apoptosis and autophagy play important roles in virus‐host interactions and innate immunity and are closely related to efficient viral replication and pathogenesis 83‐85 . Recent studies have shown that this protein can upregulate the expression of death‐associated protein kinase 1 through the nonclassical NF‐κB pathway, leading to increased phosphorylation of Beclin1 and inducing autophagy to maintain cellular homeostasis 86 . In conclusion, these data indicated that the HEV ORF3 protein can participate in multiple signaling pathways, creating favorable conditions for HEV replication.…”
Section: Orf3 Protein Regulates Host Cell Innate Immunity By Interact...mentioning
confidence: 99%
“…The HEV ORF3 protein is the smallest viral protein and plays important roles in the release of viral particles and the regulation of host immune responses, autophagy, and apoptosis. 75,80,81,86 However, because of the absence of easy-to-handle animal models and robust, universal culturing systems in vitro, the detailed roles and molecular mechanisms of the ORF3 protein in viral particle release still need to be clarified. In particular, what is the process by which the HEV ORF3 protein forms ion channels?…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%